Analysis of Pulmonary Tuberculosis Incidence in the City of Bukittinggi in 2018-2020 - Eka Budi Satria (Jurnal Minfo Polgan, 2023)
Pulmonary tuberculosis (pulmonary TB) is still a major problem of infectious diseases in Indonesia, including in the city of Bukittinggi. Data for 2022 shows that Bukittinggi City has the highest TB incidence rate in West Sumatra Province, namely 199/100.00 population. The aim of this research is to analyze the incidence of pulmonary TB in Bukittinggi City in 2018-2020. The research method was carried out using an observational descriptive design with an epidemiological approach, spatially based on Geographic Information Systems (GIS) and pulmonary TB control policies. The results showed that the highest incidence rate of pulmonary TB was in Guguk Panjang District which had the highest density, while the lowest cure rate was in Aur Birugo Tigo Baleh District.